Sosialisasi Ekspansi Model Bisnis Syariah Recycle Coconut Shell Guna Meningkatkan Ekonomi Kreatif Masyarakat Desa Kuala Lagan Kabupaten Tanjung Jabung Timur - Amir, Amri; Rafiqi; Dean Amri, Ary; Pratama, Aditya (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
This community service activity aims to fulfill daily life. Coconut is one of the superior commodities which is very abundant in Kuala Lagan Village. However, this potential has not been optimized due to the community's lack of understanding and experience in developing Recycle Coconut Shell to improve the creative economy based on the potential that the village community already has. Based on the problems above, it is necessary to increase understanding through community empowerment to support and improve the creative economy of the Kuala Lagan Village community. This program aims to develop and provide socialization and assistance to the community so that they can optimize the village's potential.